Acute toxicity analysis of LC50-96-hour (Lethal Concentration) compound of heavy metal chromium and surfactant Linear Alkylbenzene Sulfonate (Case study: zebra fish (Danio rerio)) - Kusmawati, Linda Dwi; Suprayogi, Dedy; Hakim, Abdul (Acta Aquatica: Aquatic Sciences Journal, 2025)
The decline in water quality due to the presence of chemical elements that exceed safe limits in the environment is caused by human activities. One of the main causes of pollution is the use of heavy metals such as chromium in various industries without adequate treatment, making it one of the most harmful pollutants. In addition, liquid waste containing surfactants from synthetic detergents can form foam bubbles that are difficult to remove and interfere with gas exchange between water and the atmosphere, thus exacerbating pollution. This study aims to assess the level of acute toxicity and analyze the classification of compound heavy metals Chromium (Cr) and Linear Alkylbenzene Sulfonate (LAS) that can cause death in zebrafish (Danio rerio). The research process includes the stages of adjusting the test biota, Range Finding Test (RFT), and Acute Toxicity Test (ATT). The concentrations employing in the acute toxicity test (ATT) were P1 (0 ppm), P2 (6.4 ppm), P3 (9.0 ppm), P4 (12.5 ppm), P5 (17.6 ppm), and P6 (25.6 ppm). This research is an experimental study that employing probit analysis to calculate the LC50 value. The results of acute toxicity analysis showed that the LC50 value for compound heavy metals Chromium (Cr) and LAS was 11.46 ppm. Based on the chemical hazard classification and labeling by the US EPA in 2004, this LC50 value is included in category IV, which indicates that compound heavy metals Chromium (Cr) and LAS are classified as relatively harmless. Keywords: Acute Toxicity Test; Compound Heavy Metal Chromium (Cr) and Linear Alkylbenzene Sulfonate (LAS); Lethal Concentration50; Zebra fish (Danio rerio